Flying Predators of Honeybees in Different Apiaries of Kathmandu Valley - Bhatta, Chet Prasad; Tamrakar, Ananda Shova (Journal of Natural History Museum, 2009)
An investigation on Flying Predators of Honeybees and its Management in Different Apiaries of Kathmandu valley was carried out at Bhatkyapati-12 (Apiary A) and Tyangla-3 (Apiary B), Kirtipur Municipality under apiary and field condition during July, 2004 to September, 2004. Four species of hornets belonging to family Vespidae and six species of birds of the order Passeriformes were recorded as major flying predators around the study site which consume both house and field honeybees. Hornets were observed as most serious natural enemies of bees. Among four species of hornets viz: Vespa velutina Smith, Vespa tropica L., Vespa mandarina Smith, Vespa basalis Smith; V. velutina and V. mandarina were found most abundant and serious enemies of honeybees in apiaries. Among six species of birds, Dicrurus macrocercus and Dicrurus aeneus were serious predators which heavily feed on flying honeybees during the rainy reason with high rainfall and relative humidity. Other birds recorded around the apiaries have minor effects as they consume dead bees only. Key words: Honeybees; Apiary; Predators; Hornets; Vespa; Dicrurus Journal of Natural History Museum Vol. 24, 2009 Page : 121-125 .